The influence of induced head acceleration on lower-extremity biomechanics during a cutting task - Forbes, W. O.; Dufek, J. S. (Sensors, 2024)
Sports-related concussions are caused by one substantial impact or several smaller-magnitude impacts to the head or body that lead to an acceleration of the head, causing shaking of the brain. Athletes with a history of sports-related concussion demonstrate lower-extremity biomechanics during landing tasks that are conducive to elevated injury risk. However, the effect of head acceleration on lower-extremity biomechanics during landing tasks is unknown. Twenty participants were evenly separated into a vertical hopping group and a lateral hopping group. Participants performed several land-and-cut maneuvers before and after a hopping intervention. Vertical head acceleration (g) was measured via an accelerometer during the hopping interventions. Comparisons in head acceleration during the hopping tasks were made between groups. Additionally, kinematic and kinetic variables were compared pre- and post-intervention within groups as well as post-intervention between groups. The vertical hopping group demonstrated greater vertical head acceleration compared to the lateral hopping group (p = 0.04). Additionally, the vertical hopping group demonstrated greater knee abduction angles during landing post-intervention compared to the lateral hopping group (p < 0.000). Inducing head acceleration via continuous hopping had an influence on lower-extremity biomechanics during a landing task.